THE STOCK ANALYSIS DURING COVID-19 PANDEMIC: ACTIVE AND PASSIVE STRATEGIES IN FORMING A STOCK PORTFOLIO ON THE INDONESIA STOCK EXCHANGE - Utami, Eristy M.; Arianty, Elena N.; Putri, Almanda P.; Yusvitasari, Nadya; Maharani, Virgie A.; Alrafi, M. Reyhan (CENTRAL ASIA AND THE CAUCASUS, 2022)
The purpose of this research was to determine the differences in portfolio performance based on active and passive strategies during COVID-19 pandemic. The performance measurement method used are the Sharpe, Treynor, and Jensen Index. This research was conducted on 41 company stocks that are included in the LQ 45 Index on the Indonesia Stock Exchange during the period March 2020-July 2021. The method used in compiling an active portfolio was the stock selection method with the Single Index Model approach, while the passive portfolio is formed using the Index Fund. Portfolio performance was measured monthly using the Risk Adjusted Return wich consists of the Sharpe Ratio, Treynor Ratio, Jensen Alpha methods. Statistical analysis used was Independent Sample T-test to analyze whether there is a difference between portfolio performance based on active strategy and passive strategy. Based on research conducted on the three methods (Sharpe, Treynor, Jensen Alpha) the results show that the performance of a stock portfolio based on an active strategy is better than a passive strategy on LQ 45 stocks on the Indonesia Stock Exchange during the COVID-19 pandemic for the period March 2021-July 2021.